Las definiciones de las siete artes liberales y mecánicas en la obra de Ramón Llull. The definitions of the Seven Liberal Arts and the Mechanical Arts in Ramon Llull - Ricardo Da Costa (Anales del Seminario de Historia de la Filosofía, 2006)
Being part of a post-doctoral research undertaken at the Universitat Internacional de Catalunya (Barcelona), kindly sponsored by a grant from the Generalitat de Catalunya, this article analyses the definitions and classifications pertaining to the seven liberal and mechanical arts, as presented in the following works of Ramón Lull: the Libre de contemplació en Déu (1274 1276), the Doctrina Pueril (c.1274) and the Arbre de ciència (1295-1296).